1996
DOI: 10.1002/qsar.19960150302
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Molecular Field Analysis (CoMFA) of MX Compounds using different Semi‐empirical Methods: LUMO Field and its Correlation with Mutagenic Activity

Abstract: In the present paper we make a comparison among three different semi-empirical methods (AM], MNDO and PM3) for the optimization of the geometries and calculation of different properties of MX compounds. The results were used to develop a CoMFA model to correlate the TAlOO mutagenicity of these compounds with the LUMO field. The correlations between the LUMO field and steric, electrostatic and CoMFA fields generated automatically by the SY-BYL CoMFA program, were explored. A comparison among different values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Previous CoMFA study indicated that the steric properties of MX analogues with their electron-accepting ability explain their mutagenic activity almost completely [15]. It is also shown that lowest unoccupied molecular orbital (LUMO) energy level is highly correlated with the observed mutagenicity [16]. They comprise an ideal set to test the effect of partial atomic charge variation with quantum mechanics in QSAR studies.…”
Section: Mutagen X and Its Derivatives As An Ideal Set To Test Electrmentioning
confidence: 99%
“…Previous CoMFA study indicated that the steric properties of MX analogues with their electron-accepting ability explain their mutagenic activity almost completely [15]. It is also shown that lowest unoccupied molecular orbital (LUMO) energy level is highly correlated with the observed mutagenicity [16]. They comprise an ideal set to test the effect of partial atomic charge variation with quantum mechanics in QSAR studies.…”
Section: Mutagen X and Its Derivatives As An Ideal Set To Test Electrmentioning
confidence: 99%
“…As the predictability of a QSAR model is best judged by the external validation using a test set compounds, the data set was divided into training and test sets. Training set included compounds labeled as 1,2,4,6,12,14,15,19,22,24,25,27,31,32, and 34. We adopted multiple validation strategies like LOO cross-validation and external validation.…”
Section: Molecular Electrostatic Potential Calculationsmentioning
confidence: 99%
“…model development A Bayesian model incorporated with 2D descriptors (molecular function class fingerprints of maximum diameter 6 (FCFP_6), AlogP, molecular weight, number of hydrogen bond acceptors, number of hydrogen bond donors, number of rotatable bonds, number of rings, number of aromatic rings, and molecular fractional polar surface area) was generated using DS. For Bayesian model generation, a training set of 15 compounds labeled as 1,2,4,6,12,14,15,19,22,24,25,27,31,32,34 assimilating biological and chemical diversity was developed. The 'Create Bayesian Model' protocol was used for model generation.…”
mentioning
confidence: 99%
“…For non-steroidal aromatase inhibitors related to fadrozole, Recanatini 6 observed similar models using either the AM1 method for geometry optimization and charge calculations or MAXIMIN2 molecular mechanics for geometry optimization and Gasteiger-Marsili charges. Navajas et al 7 verified that the mutagenic activity of 16 5H-furan-2-one derivatives was correlated with the LUMO field. The MNDO, PM3 and AM1 Hamiltonians were used to optimize and generate the LUMO field.…”
Section: Introductionmentioning
confidence: 95%